Metabolic disturbances in sedentary and active Polish male students with normal body mass index and waist circumference - Malara Marzena; Widłak Patrycja (Sciendo, 2024)
Study aim: To evaluate circulating lipoproteins, glucose, insulin and the index of insulin resistance (HOMA-IR) in male Polish students with normal BMI and waist circumference (WC) in the context of their physical activity.